1999
DOI: 10.3354/meps183169
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of total and active bacteria in biofilms lining tubes of the onuphid polychaete Diopatra cuprea

Abstract: Infaunal burrows and tubes support elevated levels of microbial biomass and activities relative to the surrounding bulk sediments. The impacts of these structures on sediment biogeochemistry have been intensively studled, but very little is known about the microbiota or their spatial organization within these microenvironments. Distributions of bacterial cells and microcolonies and of potentially active bacterial cells in tubes of the onuphid polychaete Diopatra cuprea were determined using confocal scanning l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Several earlier studies have indicated that the burrow wall can harbour greater number of bacterial cells than the ambient sediment (Papaspyrou et al, 2005;Kinoshita et al, 2008) and can function as a site for enhanced microbial metabolic activity (Phillips and Lovell, 1999). The phylogenetic analyses performed herein suggest that bioturbated sediment may also have higher diversity and species richness than ambient sediment and that the presence of U. deltaura or C. subterranea may result in shrimp-specific differences in bacterial community composition.…”
Section: Figurementioning
confidence: 67%
“…Several earlier studies have indicated that the burrow wall can harbour greater number of bacterial cells than the ambient sediment (Papaspyrou et al, 2005;Kinoshita et al, 2008) and can function as a site for enhanced microbial metabolic activity (Phillips and Lovell, 1999). The phylogenetic analyses performed herein suggest that bioturbated sediment may also have higher diversity and species richness than ambient sediment and that the presence of U. deltaura or C. subterranea may result in shrimp-specific differences in bacterial community composition.…”
Section: Figurementioning
confidence: 67%
“…In terms of physico-chemical characteristics, infaunal burrow walls are fairly stable environments compared to the more frequently disturbed sediment/water interface (Steward et al 1996). This stability over time allows for the development of complex microbial biofilms (Steward et al 1996, Phillips & Lovell 1999. It leads to the formation of microbial communities fundamentally different from the nearby surface and subsurface sediments, with substantial bacterial diversity and high bacterial densities and growth rates (Steward et al 1996, Dobbs & Guckert 1988a.…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing how marine deposit-feeders affect microbial variables focused on diverse species of crustaceas, holothurias and molluscs. Few reports deal with polychaetes (Aller & Yingst 1985, Duchene et al 1988, Reichardt 1988, Plante et al 1989, Plante & Jumars 1993, Steward et al 1996, Plante & Shriver 1998, Phillips & Lovell 1999. Among polychaetes, data dealing with the deposit-feeder and borrowing Hediste (Nereis) diversicolor (O.F.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are known as biogeochemical hot-spots with high organic loading, bacterial numbers, and activity (Kristensen 1988, Reichardt 1988, Hansen et al 1996, Phillips & Lovell 1999, relatively few studies have quantified and located biogeochemical reactions in the vicinity of the infaunal burrows. Direct measurements in the sediment immediately surrounding burrow structures have shown that this unique environment increases oxygen consumption (Binnerup et al 1992), hampers sulfate reduction rates (Gribsholt et al 2003, Nielsen et al 2003 and increases potential nitrification and denitrification (Kristensen 1985, Mayer et al 1995 compared to the surrounding sediment.…”
Section: Introductionmentioning
confidence: 99%